Molecular Docking Study of Substituted Benzamide Derivatives as Analgesic Candidates - Rahmawati, Rahmawati; Razak, Rais; Fawwaz, Muammar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Thiourea derivatives represent a diverse class of compounds exhibiting a range of pharmacological activities, including antitubercular, analgesic, antiviral, and anticancer effects. Of particular interest is N-allyl-N'-(benzoylcarbamothioyl)benzamide, which is hypothesized to possess analgesic properties. A comprehensive in silico molecular docking study was undertaken to evaluate this potential. In silico assays, leveraging computer simulations, are invaluable tools for predicting outcomes, generating hypotheses, and accelerating drug discovery. Molecular docking, a prominent in silico application, facilitates structure-based screening by computationally assessing the binding affinity of compounds to target proteins. This research specifically aimed to predict the analgesic activity of N-allyl-N'-(benzoylcarbamothioyl)benzamide derivatives. To achieve this, various substituents, including methyl, methoxy, tert-butyl, dimethylamino, and halogens, were strategically incorporated at the ortho, meta, and para positions of the benzoylcarbamothioyl ring, generating a library of novel analgesic drug candidates. Compound activity was primarily evaluated using the rerank score. Additionally, ProTox-3.0 and pkCSM were utilized to predict these synthesized compounds' toxicity and physicochemical properties. Initial findings were encouraging, with 18 derivatives of N-allyl-N'-(benzoylcarbamothioyl)benzamide demonstrating enhanced predicted analgesic activity. Among these, six compounds exhibited promising analgesic properties without predicted toxicity. In conclusion, these in silico results suggest that certain N-allyl-N'-(benzoylcarbamothioyl)benzamide derivatives hold significant promise as potential analgesic agents, warranting further validation through subsequent laboratory and in vivo investigations.